PERTARUNGAN “REALITAS” DALAM FILM: Analisis Cyberspace Film “Transcendence” - Syafi'i, Muhammad; Latifah, Nor (LENTERA: Jurnal Ilmu Dakwah dan Komunikasi, 2018)
Humanity in the today’s modern age linked closely to information and communication technology. Advancements in the area of information and communication technology have changed the very basis of human interactions, including the way people make sense of reality. The presence of cyberspace as a second life of humans, according to Mark Slouka, has led to three different understandings of reality, namely: destopian which views pessimistically, optimistic neofuturists, and more critical techno-realists. In this paper, the author will present one reflection on cyberspace displayed in a Movie by Wally Pfister called "Transcendence". This research applies qualitative method by observing scences featuring in the movie. Findings reveal that virtual reality displayed in "Transcendence" falls into the category of neofuturists. This conclusion is obtained based on identification of the representation of reality, identity, community, and space displayed.Keywords: Film, cyberspace, neofuturists.